Analysis of VOC emissions and O3 control strategies in the Fenhe Plain cities, China. (1st January 2023) - Liu, Yafei; Qiu, Peipei; Xu, Kai; Li, Chenlu; Yin, Shijie; Zhang, Yunjun; Ding, Yu; Zhang, Chen; Wang, Zheng; Zhai, Ruixiao; Deng, Yijun; Yan, Fengyu; et al.
Abstract: Long-term continuous hourly measurements of ambient volatile organic compounds (VOCs) are scarce at the regional scale. In this study, a one-year hourly measurement campaign of VOCs was performed in Lvliang, Linfen, and Yuncheng in the heavily polluted Fenhe Plain region in China. The VOC average (±standard deviation, std) concentrations in Lvliang, Linfen, and Yuncheng were 44.4 ± 24.9, 45.7 ± 24.9, and 37.5 ± 25.0 ppbv, respectively. Compared to published data from the past two decades in China, the observed VOCs were at high concentration levels. VOCs in the Fenhe Plain cities were significantly impacted by industrial sources according to calculated emission ratios but were less affected by liquefied petroleum gas and natural gas (LPG/NG) and traffic emissions than those in megacities abroad. The emission inventories and observation data were combined for verification and identification of the key VOC species and sources controlling ozone (O3 ). Industrial emissions were the largest source of VOCs, accounting for 65%–79% of the total VOC emissions, while the coking industry accounted for 45.2%–66.0%. The emission inventories significantly underestimated oxygenated VOC (OVOC) emissions through the verification of VOC emission ratios. O3 control scenarios were analyzed by changing VOC/NOX reduction ratios through a photochemical box model. O3 control strategies were formulated considering local pollution control plans, emission inventories, and O3 formation regimes. The O3 reduction of reactivity-control measures was comparable with emission-control measures, ranging from 16% to 41%, which was contrary to the general perception that ozone formation potential (OFP)-based measures were more efficient for O3 reduction. Sources with high VOC emissions are accompanied by high OFP on the Fenhe Plain, indicating that the control of high-emission sources can effectively mitigate O3 pollution on this region. Graphical abstract: Image 1 Highlights: A one-year hourly VOC measurement was performed in multiple cities in China. The observed VOC concentrations were comparable with other Chinese cities. The coking industry plays an important role in VOC emissions in this region. The O3 reduction estimates based on reactivity and emission measures were similar.